Retracted: Junk Food Consumption, Perceptions and Associated Factors among the Private School Children - Acharya, Shiva R.; Pahari, Sandip; Moon, Deog H.; Shin, Yong C. (Current Nutrition & Food Science, 2021)
This article has been retracted at the request of the authors and Editor-in-Chief. Authors were unable to conclude the manuscript appropriately. Bentham Science apologizes to the readers of the journal for any inconvenience this may have caused. The Bentham Editorial Policy on Article Retraction can be found at https://benthamscience.com/editorial-policies-main.php. BENTHAM SCIENCE DISCLAIMER: It is a condition of publication that manuscripts submitted to this journal have not been published and will not be simultaneously submitted or published elsewhere. Furthermore, any data, illustration, structure or table that has been published elsewhere must be reported, and copyright permission for reproduction must be obtained. Plagiarism is strictly forbidden, and by submitting the article for publication, the authors agree that the publishers have the legal right to take appropriate action against the authors, if plagiarism or fabricated information is discovered. By submitting a manuscript, the authors agree that the copyright of their article is transferred to the publishers if and when the article is accepted for publication.